2014
DOI: 10.1089/jmf.2013.3084
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effects ofSynsepalum dulcificum: A Review

Abstract: Synsepalum dulcificum or the "miracle fruit" is well known for its taste-modifying ability. The aim of this review was to assess the published medically beneficial as well as potential characteristics of this fruit. A search in three databases, including PubMed, ScienceDirect, and Google Scholar, was made with appropriate keywords. The resulting articles were screened in different stages based on the title, abstract, and content. A total of nine articles were included in this review. This review summarized the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 23 publications
0
21
0
Order By: Relevance
“…The fruit of the plant is small, ellipsoid, bright red, and berry‐liked. The fruit possess a unique ability to turn sour foods to sweet by affecting the taste buds of the tongue (Swamy, Suwaibah Abd, Muniandy, & Mallikarjuna Rao, 2014). Due to this unusual property, the natives also call it as miracle fruit or miracle berry.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fruit of the plant is small, ellipsoid, bright red, and berry‐liked. The fruit possess a unique ability to turn sour foods to sweet by affecting the taste buds of the tongue (Swamy, Suwaibah Abd, Muniandy, & Mallikarjuna Rao, 2014). Due to this unusual property, the natives also call it as miracle fruit or miracle berry.…”
Section: Introductionmentioning
confidence: 99%
“…Due to this unusual property, the natives also call it as miracle fruit or miracle berry. In Africa, the Miracle fruit has been historically used for treating diarrhea in humans and animals because both its skin and pulp have high content of flavonoid compounds (Inglett & Chen, 2011; Ntie‐Kang et al, 2013; Swamy et al, 2014). The US Food and Drug Administration (FDA) have accepted the fruit used as an additive because it contains a natural orange‐red color.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Miraculin does not activate these receptors until subjected to an acidic pH, generally, between pH 3.0 and 6.0. 29 The possible mechanism of miraculin in the modification of taste is shown in Figure 9.…”
Section: Mechanism Of Taste Modifying Activity Of Miraculinmentioning
confidence: 99%
“…It is noteworthy that all parts of this plant have medicinal importance [9]. However, Swamy et al [10] found that few studies had been done on the medical or clinical effects of miracle fruit aside from well-established studies on the sweetening effects [11]. Inglett and Chen [12] investigated the antioxidant properties of phenolics and flavonoids in the skin, pulp, and seeds of miracle fruit and suggested it as a good source of antioxidants for functional food applications.…”
Section: Introductionmentioning
confidence: 99%